The global cloud operation system model - Замковець, Іван Володимирович (Новітні інформаційні системи та технології, 2016)
The article describes new approach to resolve the problem of distribution the parallel application among multiple cloud services. This new approach is creating new special program level between user applications and cloud services, which task is control and distribution cloud resources.